Pause procedure to enhance learning during the lectures in Medical Colleges - Chaudhry, Zafar Ali; Malik, Muhammad Tahir Bashir; Ayub, Ayesha; Khan, Aamir Imtiaz; Anwar, Moin; Shakeel, Mahnoor (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Lectures are still the most appropriate and practical way of conveying knowledge in available limited resources but their effectiveness is very debatable. The pause procedure is a strategy that uses strategic pauses in a lecture to help students overcome this problem. The objective of this study was to analyze the effectiveness of pausing to enhance learning during lectures in medical colleges. METHODOLOGY: After institutional permission # 48.ERC/FMU/2023-24.384, this comparative cross-sectional study was conducted on fourth-year MBBS students (the whole Batch was involved, which comes to the urology ward) in a public sector medical institution. The technique of taking a clarification pause during the long sessions (equal to or more than 45 minutes) was utilized and feedback was taken. RESULTS: Student satisfaction was described by 75% of students in Method-A (taught with pausing technique) and 48% of the students in Method-B (taught without pausing) (p=0.018). Maintaining the attention span till the end of the lecture was described by 74% of Method-A and 34% of Method-B students (p≤0.001). Clarity of the topic was described by 82% with A and 51 % with B students(p≤0.001). The mean MCQ score of the students group after method A was 62% and 52% with B. CONCLUSION: The pause procedure is an effective methodology to improve learning and academic performance in undergraduate medical students without causing any added burden.